Historical and contemporary hypotheses on the development of oral diseases: are we there yet? - Rosier, Bob T.; De Jager, Marko; Zaura, Egija; Krom, Bastiaan P. (Frontiers in Cellular and Infection Microbiology, 2014)
Dental plaque is an oral biofilm that much like the rest of our microbiome has a role in health and disease. Specifically, it is the cause of very common oral diseases such as caries, gingivitis, and periodontitis. The ideas about oral disease development have evolved over time. In the nineteenth century, scientists could not identify bacteria related to disease due to the lack of technology. This led to the “Non-Specific Plaque Hypothesis” or the idea that the accumulation of dental plaque was responsible for oral disease without discriminating between the levels of virulence of bacteria. In the twentieth century this idea evolved with the techniques to analyze the changes from health to disease. The first common hypothesis was the “Specific Plaque Hypothesis” (1976) proposing that only a few species of the total microflora are actively involved in disease. Secondly, the “Non-Specific Plaque Hypothesis” was updated (1986) and the idea that the overall activity of the total microflora could lead to disease, was enriched by taking into account difference in virulence among bacteria. Then, a hypothesis was considered that combines key concepts of the earlier two hypotheses: the “Ecological Plaque Hypothesis” (1994), which proposes that disease is the result of an imbalance in the microflora by ecological stress resulting in an enrichment of certain disease-related micro-organisms. Finally, the recent “Keystone-Pathogen Hypothesis” (2012) proposes that certain low-abundance microbial pathogens can cause inflammatory disease by interfering with the host immune system and remodeling the microbiota. In this comprehensive review, we describe how these different hypotheses, and the ideas around them, arose and test their current applicability to the understanding of the development of oral disease. Finally, we conclude that an all-encompassing ecological hypothesis explaining the shifts from health to disease is still lacking.